2000
DOI: 10.1023/a:1006421112839
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our data suggest that MMP-2 is associated with histological malignancy and poor survival in brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Further, these model results suggest exploration of invasion-specific markers (e.g. MMP-2 (33), vimentin (34)) may enhance the prognostic accuracy of the current grading scheme. Admittedly, assessing invasion from fixed histological sections of dead tissue is a true challenge.…”
Section: Discussionmentioning
confidence: 93%
“…Further, these model results suggest exploration of invasion-specific markers (e.g. MMP-2 (33), vimentin (34)) may enhance the prognostic accuracy of the current grading scheme. Admittedly, assessing invasion from fixed histological sections of dead tissue is a true challenge.…”
Section: Discussionmentioning
confidence: 93%
“…In one study of brain metastasis, MMP-2 was identified in all metastases regardless of site of origin. Moreover, MMP-2 activity correlated inversely with survival [55]. In a murine tumor model, the incidence of brain metastasis was reduced by 75% when compared to the wild type following the use of tissue inhibitor of metalloprotease1 (TIMP-1), which suggests that inhibitors of MMPs suppress BrMs [56].…”
Section: The Metastatic Processmentioning
confidence: 99%
“…The biological role and functional contribution of MMPs is complex and their role in meningiomas is far from established. Previous studies have focused on establishing the role of MMP2 in meningiomas, in particular as it relates to tumor recurrence, brain invasion, and peritumoral edema, and the data is conflicting [10, 19, 21, 23, 24, 26, 2831, 48]. Though some studies found higher MMP2 expression levels in recurrent meningiomas [28, 48], others have found no association between meningioma grade and MMP2 levels [29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on the predictive potential of MMP2 on meningioma peritumoral edema have been contradictory, with Paek et al [30] suggesting a positive association, whereas Panagopolous et al [31] noted no such association. Yet Jaalinoja et al [19] found no MMP-2 expression in benign meningiomas altogether.…”
Section: Discussionmentioning
confidence: 99%